2016
DOI: 10.1007/s11101-016-9470-4
|View full text |Cite
|
Sign up to set email alerts
|

Current knowledge of Schisandra chinensis (Turcz.) Baill. (Chinese magnolia vine) as a medicinal plant species: a review on the bioactive components, pharmacological properties, analytical and biotechnological studies

Abstract: Schisandra chinensis Turcz. (Baill.) is a plant species whose fruits have been well known in Far Eastern medicine for a long time. However, schisandra seems to be a plant still underestimated in contemporary therapy still in the countries of East Asia. The article presents latest available information on the chemical composition of this plant species. Special attention is given to dibenzo cyclooctadiene lignans. In addition, recent studies of the biological activity of dibenzocyclooctadiene lignans and schisan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
215
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(226 citation statements)
references
References 107 publications
0
215
1
5
Order By: Relevance
“…The major constituents of the fruit extract of S. chinensis are lignans, a large group of naturally occurring phenols classified into several group according to their chemical structure. The fruit extract of S. chinensis (but also leaves and stems) especially contains lignans with dibenzocyclooctadiene skeleton, such as schisandrol, schisantherin A, deoxyschisandrin, schisandrin B and schisandrin C [116], and with tetrahydrofuran structure, such as D-epigalbacin, machilin G and chicanine [117]; several scientific studies demonstrated the antioxidant activity of these compounds [115,117,118]. Some recent studies have also shown the presence in fruits and leaves of S. chinensis of phenolic compounds with good antioxidant activity, such as chlorogenic acid, isoquercitrin and quercitrin [115,119].…”
Section: Schisandra Chinensismentioning
confidence: 99%
See 1 more Smart Citation
“…The major constituents of the fruit extract of S. chinensis are lignans, a large group of naturally occurring phenols classified into several group according to their chemical structure. The fruit extract of S. chinensis (but also leaves and stems) especially contains lignans with dibenzocyclooctadiene skeleton, such as schisandrol, schisantherin A, deoxyschisandrin, schisandrin B and schisandrin C [116], and with tetrahydrofuran structure, such as D-epigalbacin, machilin G and chicanine [117]; several scientific studies demonstrated the antioxidant activity of these compounds [115,117,118]. Some recent studies have also shown the presence in fruits and leaves of S. chinensis of phenolic compounds with good antioxidant activity, such as chlorogenic acid, isoquercitrin and quercitrin [115,119].…”
Section: Schisandra Chinensismentioning
confidence: 99%
“…Schisandrin also exhibits anti-inflammatory activity [120,121], and S. chinensis fruit extract has been reported to reduce pro-inflammatory cytokine levels in THP-1 cells stimulated with P. acnes and to protect UVB-exposed fibroblasts from photoaging [122]. Due to these biological properties, the extract from S. chinensis fruits has beneficial effects on the skin [118], and has been proposed as a cosmetic anti-pollution ingredient (Table S2, Ingredient No. 10, Urbalys ® ).…”
Section: Schisandra Chinensismentioning
confidence: 99%
“…Magnolia-vine is a medicinal plant which is widely used in medicine as a valuable source of biologically active substances (BAS), such as vitamins of the , and groups, organic acids, pectins, and aromatic substances [Chun et al 2014, Szopa 2017. The major BAS in magnolia-vine are lignans, mainly schizandrin, -schizandrin and schizandrol, which can be found in all parts of the plant [Wang et al 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Modern research highlighted that S. chinensis has antitumor 14 , antihepatotoxic and hepatoprotective 15,16 , anti-cancer 17 , neuroprotective 18 , anti-diabetic 19 , and antioxidant 17,20 properties. So far, its most important bioactive compounds are thought to be lignans, derivatives of dibenzocyclooctadiene, especially schisandrin (schisandrol A), schisandrol B, schisandrin A and schisandrin B 12,21 which are mainly present in the fruits. However, besides lignans, recently phenolic compounds and triterpenoids were identified in leaves and stems of S. chinensis showing promising bioactivities 22,23 .…”
Section: Introductionmentioning
confidence: 99%